Is antibiotic prophylaxis really needed in thyroid surgery? - Mehta, Rachna B.; Yadav, Rajesh; Jain, Akansha; Ashwathy, K. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Thyroid surgery is considered under clean surgical procedures and antibiotics are not routinely recommended for such clean surgical procedures. However, many hospitals in India still give post-operative antibiotics to thyroidectomy patients. Our aim was to find out if administering antibiotics in thyroid surgeries really helpful? Methods: A retrospective study was conducted for a period of one year with total number of 30 participants, 15 of which were given antibiotic prophylaxis and remaining 15 weren’t given. The patients were observed for signs of infection and hence need for antibiotics till one month postoperatively. Results: None of the patients in both the groups with and without antibiotics developed post-operative surgical site infection necessitating the need for antibiotics. Conclusions: Thyroid surgery being classified as clean surgical procedure with small incision and short duration and given that strict aseptic precautions are followed in surgery, then antibiotic prophylaxis may not be needed. However, our study should be considered as only a preliminary case control study and a larger prolonged study is needed to provide statistically significant data.